Correlates of Alcohol-Related Regretted Sex among College Students - Orchowski, Lindsay M. (2012)
The prevalence of alcohol-related regretted sex in college students warrants a better understanding of the characteristics of students who report such experiences. Therefore, the present study examined correlates of regretted sexual experiences involving alcohol use among two specific high-risk college student samples: Students mandated to alcohol intervention (N = 522) and volunteer first-year students transitioning to college (N = 481). Results indicated that alcohol-related regretted sex occurred in similar rates in mandated and volunteer students, with approximately 25% of the students reporting at least one occurrence in the past month. Women were more likely to report alcohol-related regretted sex compared to men. The belief that alcohol use would result in “liquid courage” was associated with alcohol-related regretted sex among college students, even after accounting for greater alcohol use and problem alcohol use behaviors. These findings have significant implications for intervention efforts and future research.